Earthquake-induced loss assessment of steel buildings designed to Eurocode 8. (1st April 2020) - Silva, A.; Macedo, L.; Monteiro, R.; Castro, J.M.
Highlights: The seismic performance of EC8-compliant steel MRF and CBF buildings is examined. The need for revisions of EC8 towards better seismic performance is emphasized. Contributions towards the use of loss-driven seismic designs in EC8 are detailed. Abstract: The main objective of this paper is to understand and characterize the level of expected earthquake-induced economic losses of steel buildings designed to Eurocode 8. This is attained through the use of a comprehensive population of case-study buildings that considers different lateral load resisting systems, plan configurations and building heights. Different locations of low and high seismicity, reflecting the majority of the European seismic reality, are considered. The results indicate that EC8-compliant steel moment-resisting frame (MRF) buildings and concentrically-braced frame (CBF) buildings generally exhibit good seismic performance in terms of mean annual frequency of reaching collapse. Although all buildings showed good performance against collapse, when compared to the requirements present in literature, clear indications on a lower performance of chevron-braced CBFs are observed. Furthermore, low expected annual losses (EALs) are recorded across the population of steel buildings considered, with a predominant contribution of losses coming from structural and non-structural damage. Based on the findings reported in this paper, different insights towards the incorporation of loss performance objectives in the European seismic design code are provided.